(untitled) (The Peerian Journal, 2024)
This article examines the theoretical foundations and practical aspects of managing the wage and benefit system in modern economic conditions. Particular attention is paid to the analysis of various theoretical approaches and techniques, as well as the practical application of this knowledge in various sectors of the economy, including the banking sector.